THE HUMAN ECOLOGY OF A FORMER STATE-OWNED-ENTERPRISE IN WESTERN ANATOLIA - Çaya, Sinan (International Journal of Research -GRANTHAALAYAH, 2015)
This article is basically the retrospective investigation of a Turkish State-owned pulp-and-paper plant, in the time interval of 1979-1981. At the time, the mixed economy understanding prevailing, many industrial installations were operated by the government in Turkey. Along the course of privatizations the vast majority of such institutions have changed hands and the few remaining ones are also on the same way.